Effect of fulleroid materials on the mechanical and tribological properties and dielectric relaxation of polyamide 6 nanocomposites. (17th February 2016) - Sinitsin, Alex N.; Zuev, Vjacheslav V.
Abstract: The effect of fulleroid materials (fullerene С60 and fullerene soot, which is used for fullerenes production) on the mechanical and tribological properties of polymer nanocomposites based on polyamide 6 (PA6) was investigated. Composites were synthesized by direct mixing in an extruder. The use of the nanoparticles was an effective way to decrease the friction coefficient of the polymer composites because the fillers had the same size as the segments of the surrounding polymer chains. The steady state coefficients of friction with addition of fulleroid fillers were lower than that of unfilled PA6. The lowest coefficient of friction was observed for PA6 filled with 1 wt% fullerene soot. Dielectric spectroscopy was used to investigate the influence of nanoparticles on the relaxation processes in the polymer matrix. It is found that the segmental relaxation processes become faster with the addition of fullerene С60 . In contrast, the secondary processes of PA6/fullerene C60 nanocomposites were observed to slow down with the addition of fullerene C60 . This means that the local "molecular stiffness" is increased, and a phenomenological link between the secondary relaxation times and the mechanical properties explains the increase in the Young's modules of the nanocomposites upon the addition of С60 . These observations suggest that nanoparticles can have a qualitatively different effect on the matrix polymer dynamics at different length scales, and caution must be taken in comparing the changes in the dynamics associated with different relaxation processes. Copyright © 2016 John Wiley & Sons, Ltd.